(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
We begin with historical narratives that represent Nepal-India ties as being built on historical, cultural, economic, and geopolitical dimensions and mutual respect of sovereignty. The Nepal-India relationship is complex and multifaceted, with historical, cultural, economic, and geopolitical dimensions. A liberal and realistic view on this relationship in the contemporary geopolitical context would involve acknowledging both the positive aspects of cooperation and addressing the challenges that have emerged over time. A liberal perspective would emphasize the deep cultural and historical ties between Nepal and India. They both share social, economic, and political advancement. Problems, hazards, and uncertainties have been brought about as a result of globalization in relation to the flow of people, products, and capital. Because of this, border governance has developed among states, which necessitates the cooperation of neighboring states in the development of border management systems. The research was a qualitative study that followed the "practice turn" in International Relations (IR) and took into consideration human actions that affect social realities. The research focused on the open border between Nepal and India during this time period. According to the research, the open border that exists between Nepal and India provides a number of specific benefits along with risks and challenges. Within this essay, a concise explanation of border government is provided. It describes theories and techniques, as well as recommends border governance for open borders between Nepal and India. The issues of border governance for Nepal-India boundaries is emphasized in the study, which acknowledges the existence of border disputes and significant footraces.